Philips Glass Bulbs, Inc. - Adriano, Angie; Gomez, Au; Oliva, Nony; Padriga, Vic; Sy, Vincent (College of Engineering, 1989)
The Philips Glass Bulbs,Inc. is the only firm in the country that manufactures glass for lamps and bulbs.Currently,it has achieved its market gola and now aims to maintain it for sometime.However,the volume of locally manufactured glass is still not enough to meet its demand.The company imports around 50% of its requirements.The plant is located in Pamplona,Las Pinas,Metro Manila,occupying a total land area of more than 30,000 square meters.It started its operations in 1956 and today,it runs continuously,24 hours a day,7days a week.Working condition in plant are in general satisfactory but this however does nt mean that no further improvements can be made.The plant is operating at maximum capacity with budgeted efficiencies of 94% and 85% for production and hourly efiiciencies,respectively.Most of the equipments are highly sophisticated especially those that monitor the performance of the furnace,bulb-blowing equipment(carousel)and the tube drawing machine.Raw materials have two sources, the foreign and local suppliers.Silica sand which is one other major constituent of the input mixture is imported yearly since the type of sand that is locally available does not meet specifications that are called for in glass-making.Cullets broken glass are also important ingredients.They act as a catalyst in melting process.Locally available materials are given a lead time of 1 to 2 weeks when procuring.An inventory level that is good for one month's consumption is maintained for local materials while supply good for at least six months is kept for imported materials.Finished goods inventory is maintained at a minimum of one million bulbs.The glass making process start with the furnace which is operating at more than 2000F melting the mixture of sand,cullet's and chemicals.The furnace can hold 400 kg.per hour of the mixture.Two-thirds goes to the bulb blowing-blowing machine and the rest to the tube-drawing line.The carousel produces the bulbs and the glass tubes are produced by the tube drawing machine equipment with a mandrel that draws the hot tubes out of machine to a line that is more than 30 feet long.The bulbs are force-cooled by blower.They are transported by conveyors to the inspecting and packing areas.The tubes however,are glazed (to smoothen the edges) before they are inspected and packed.A central purchasing unit handles all the acquisition of raw materials and spare parts.A maintenance department is responsible for keeping the whole operating at the desired level of performance,i.e.,to keep the equipment's running efficiently.The glass factory has its own standard quality control procedure and follows it rigidly since the company believes that its name stands for quality.For more than a decade now,50% of company's glass requirement for light bulb is imported.This has opened doors for possible expansion.The rate of production for glass tubes,however,seem adequate enough to meet the demand.Also,if the capacity of the tube drawing machine is increased,this will ball for a longer tube drawing line,a bigger plant for that matter.Also,management sees that such an increase is uncalled for.Nevertheless,the capacity of the bulb blowing machine can be increase.Today,five countries have refrained from using the carousel to produce bulbs.They now what is known as the caribou.Its capacity ranges from 4000 to 10,000 bulbs per hour.By increasing the capacity of the said section,the possibility of a furnace expansion should be considered.Computations have shown that only 2% increase is necessary which the group perceived as insignificant.Thus,furnace does not have to be changed.Work levels have to be maintained because of the influence of the labor union but re-assignment and training of a number of key personnel have to be done.With such a step,a 55% decrease on imported glass bulbs will result-significant decrease on import dependence.Since the plant has been operating for quite some time (currently on a stable state),most of the areas like materials hanling,materials flows,quality control procedure and others of similar nature are operating smoothly and efficiently,therefore,only minor revisions are recommended.